First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations EXHIBITIONS "DAILY MAIL" EFFICIENCY EXHIBITION, OLYMPIA, LONDON. Through the generosity of our Vice-President, Viscount Northcliffe, The People's League of Health was an Exhibitor at the "Daily Mail" Efficiency Exhibition, Olympia, from February 10th to 26th, 1921. The Hon. Organiser invited the following organisations to co-operate with the League in its Exhibit :— The Food Education Society. The Garden Cities and Town Planning Association. National Baby Week Council. National Council for Combating Venereal Disease. National Council of Women — Child Welfare Travelling Exhibit. National Institute of Industrial Psychology. National Institute of Health, Maternity and Child Welfare. Village Clubs Association. Blind Babies' Branch of the National Institute for the Blind, Institute of Hygiene. The Women's Imperial Health Association. Thanks are due to the Medical Officer of Health of Glasgow, Dr. Chalmers, for the loan of some interesting charts regarding the effect of the one-, two- and three-roomed homes upon the development, mental and physical, of children, together with a plaque visualising that chart ; also charts relative to food and its effect on development of children. The Exhibit was visited by a great number of people. The King and Queen honoured us with a visit on Monday, February 21st, at 9.30 a.m., and Their Majesties were received by Professor Sir German Sims Woodhead, representing the Medical Council of the League, and the Hon. Organiser. The Rt. Hon. J.R Clynes, M.P., was unavoidably prevented from receiving Their Majesties as representative of the Lay Council of the League. Among the notable people who visited the Exhibit were the Minister of Health (the Rt. Hon. Dr. Addison), the Chief Medical Officer of Health (Sir George Newman), the Rt. Hon. John Burns, and representatives of many of the Embassies. Dr. Addison and Sir George Newman asked for copies of the chart and plaque, loaned by Dr. Chalmers, to be sent to them. This was done. At a luncheon given by the Exhibitors to those who organised the Exhibition, at which Sir Andrew Caird presided, the Earl of Bessborough, representing the Middlesex Hospital Exhibit at the Exhibition, proposed a vote of thanks to Viscount Northcliffe for the opportunity given to health organisations at the "Daily Mail" Efficiency Exhibition. The Hon. Organiser, as representative of the People's League of Health Exhibit, was asked to second the vote of thanks to Lord Northcliffe ; which she did. The Exhibit evoked considerable general and public interest, and resulted in numerous enquiries for our literature, details of our organisation and work from representatives (official and lay) of India, Cape Colony, Australasia, Japan, Siam, Czecho-Slovak States and Norway. A great deal of literature and many autograph Souvenirs of the League were sold. March, 1922. Southend Rotary Industrial Exhibition. The League took part in this Exhibition. 16 200/B/3/2/C693/1/71